INDEPENDENCE IN LEARNING MATHEMATICS IN GRADE II SDN 2 CIBEUTI: COMPARISON BETWEEN PJBL AND PBL STRATEGIES - Gumilar, Gumgum; Sutama, Sutama; Markhamah, Markhamah (Nindikayla Institute, 2024)
The aim of this study is to describe a project-based learning strategy (PjBL) with Problem-based Learning (PBL) towards reviewed learning independence from student discipline. The research method used in this study is Quantitative with the model or approach of quasi-experimental design (pretest-posttest) as the design. The study was conducted from March to July 2023 in Class II SDN 2 Cibeuti, Tasikmalaya, West Java. Counting is the chosen learning material. Data collection techniques use tests and nontes. In this study, the test (pretest-posttest) is a double-choice test, while the non-test consists of documentation, interviews with teachers, and student discipline observation sheets. These are all used to evaluate learning processes and outcomes, including student activities. With a total of 25 students in the experimental and control classes. The data analysis techniques used are obtained from the test results of the independent value of learning mathematics as well as from the use of statistics. Data analysis techniques to test the hypothesis of independent learning mathematics results pre-testposttest using SPSS 25 for Windows Data from the research results showed that class II students at SDN 2 Cibeuti, Tasikmalaya, had significant learning independence when implementing PjBL and PBL strategies. In an effort to improve the independence of students in class II on math subjects in SDN 2 Cibeuti, statistical tests showed that the significance of posttest results in both classes is less than 0.05. Analysis of the results of independent mathematical learning showed significant improvements using PjBL strategies in the experimental class, with an average posttest score (96.00) higher than the mean posttest value for the PBL strategy in the control class (62.40). The results of this study show that the PjBL strategy is more effective than the PBL strategy. Therefore, it can be concluded that the project-based learning strategy (PjBL) is effective.